Improved passivation depth of porous fluorescent 6H-SiC with Si/C faces using atomic layer deposition. (1st March 2022) - Yanai, Kosuke; Lu, Weifang; Yamane, Yoma; Kodera, Keita; Ou, Yiyu; Ou, Haiyan; Kamiyama, Satoshi; Takeuchi, Tetsuya; Iwaya, Motoaki; Akasaki, Isamu
Abstract: We investigated the effects of different growth facets of 6H-SiC and different voltage waveforms on the porous structure and luminescence properties. The structure formed on the surface after anodic etching significantly changed because of the difference in the growth plane, whereas dendritic and columnar pores were observed inside the Si- and C-face samples. These large porous structures were shown to promote the penetration depth of the atomic-layer-deposited Al2 O3 films, and a recorded passivation depth of 30 μ m layer was confirmed in C-face porous SiC. From the results using a fluorescence microscope and photoluminescence spectra measurement, it was concluded that the pulsed-voltage etching was preferable for fabricating uniform porous structures compared with the constant-voltage etching. However, the enhancement of the luminescence intensity needs to be further improved to realize high luminescent efficiency in porous fluorescent SiC.